Optimization of Multimeric Human Papillomavirus L2 Vaccines - Jagu, Subhashini (Public Library of Science, 2013)
We sought to define the protective epitopes within the amino terminus of human papillomavirus (HPV) type 16 minor capsid protein L2. Passive transfer of mice with rabbit antisera to HPV16 L2 peptides 17–36, 32–51 and 65–81 provided significant protection against vaginal HPV16 challenge, whereas antisera to 47–66, 108–120 or 373–392 did not. Vaccination with L1 virus-like particles induces a high titer, but generally type-restricted neutralizing antibody response. Conversely, vaccination with L2 11–88, especially multimers thereof, induces antibodies that neutralize a broad range of papillomavirus types, albeit at lower titers than for L1 VLP. With the intent of enhancing the immunogenicity and the breadth of protection by focusing the immune response to the key protective epitopes, we designed L2 fusion proteins consisting of residues ∼11–88 of eight divergent mucosal HPV types 6, 16, 18, 31, 39, 51, 56, 73 (11–88×8) or residues ∼13–47 of fifteen HPV types (13–47×15). The 11–88×8 was significantly more immunogenic than 13–47×15 in Balb/c mice regardless of the adjuvant used, suggesting the value of including the 65–81 protective epitope in the vaccine. Since the L2 47–66 peptide antiserum failed to elicit significant protection, we generated an 11–88×8 construct deleted for this region in each subunit (11–88×8Δ). Mice were vaccinated with 11–88×8 and 11–88×8Δ to determine if deletion of this non-protective epitope enhanced the neutralizing antibody response. However, 11–88×8Δ was significantly less immunogenic than 11–88×8, and even the addition of a known T helper epitope, PADRE, to the construct (11–88×8ΔPADRE) failed to recover the immunogenicity of 11–88×8 in C57BL/6 mice, suggesting that while L2 47–66 is not a critical protective or T helper epitope, it nevertheless contributes to the immunogenicity of the L2 11–88×8 multimer vaccine.